Investigating Students' Perceptions of Open Peer Review to Improve Their Writing Ability: A Study at SMP Taman Siswa Padang - Sasria, Siwi; Wahyuni, Delvi (Universitas Negeri Padang, 2024)
This research is a quantitative descriptive research aimed to find out students' perceptions of the application of open peer review in English writing learning in class. The population is ninth-grade students at SMP Tamansiswa Padang with all students selected as samples based on the total sampling technique. This study focuses on students' overall perceptions, effectiveness and the role of open peer review in writing learning. In order to collect data, the researcher used a questionnaire. This questionnaire was adapted from Tahir (2018). The results of the data analysis shows that students have a positive perception of the contribution of open peer review in the learning of writing based on the reviews given, providing more opportunities to practice and discuss, and the creation of a relaxed and stress-free learning environment. This research shows that open peer review works as a valuable tool in improving students' writing abilities and can be adopted in writing lessons.